Probiotic bacteria can modulate immune responses to paratuberculosis vaccination - Oyanguren, Maddi; Molina, Elena; Mugica, Maitane; Ladero-Auñon, Iraia; Fuertes, Miguel; Fernández, Miguel; Benavides, Julio; Elguezabal, Natalia (Frontiers in Cellular and Infection Microbiology, 2024)
Mycobacterium avium subsp. paratuberculosis (Map) is the etiological agent of paratuberculosis (PTB), a chronic intestinal inflammatory disease that causes high economical losses in dairy livestock worldwide. Due to the absence of widely available preventive or therapeutical treatments, new alternative therapies are needed. In this study, the effect of a probiotic alone or in combination with a commercial vaccine has been evaluated in a rabbit model. Vaccination enhanced the humoral response, exerted a training effect of peripheral polymorphonuclear neutrophils (PMNs) against homologous and heterologous stimuli, stimulated the release of pro-inflammatory cytokines by gut-associated lymphoid tissue (GALT) macrophages, and reduced the bacterial burden in GALT as well. However, the administration of the probiotic after vaccination did not affect the PMN activity, increased metabolic demand, and supressed pro-inflammatory cytokines, although humoral response and bacterial burden decrease in GALT was maintained similar to vaccination alone. The administration of the probiotic alone did not enhance the humoral response or PMN activity, and the bacterial burden in GALT was further increased compared to the only challenged group. In conclusion, the probiotic was able to modulate the immune response hampering the clearance of the infection and was also able to affect the response of innate immune cells after vaccination. This study shows that the administration of a probiotic can modulate the immune response pathways triggered by vaccination and/or infection and even exacerbate the outcome of the disease, bringing forward the importance of verifying treatment combinations in the context of each particular infectious agent.